Hubungan Antara Perceived Organizational Support dengan Beban Kerja pada Kurir Mitra Shopee Express di Kota Padang - Ferguson Situmorang, Roy; Pratama, Mario (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the relationship between perceived organizational support and workload on Shopee Express courier partners in Padang City. This study uses a quantitative research method with a correlational approach. The data collection technique in this study uses a questionnaire with a Likert scale as a measuring tool for the research instrument. Some conclusions are as follows: (a) The workload of Shopee Express courier partners in Padang City is generally in the low category. This is indicated by the empirical mean value of the workload which is lower than the hypothetical mean, as well as the categorization results which show that the majority of respondents are in the low category. However, there are still respondents who are in the medium and high categories, which indicates a variation in work demands felt by courier partners; (b) Perceived Organizational Support (POS) on Shopee Express courier partners is generally in the high category. This is reflected in the empirical mean value of Perceived Organizational Support (POS) which is higher than the hypothetical mean, as well as the categorization results which show that most respondents perceive good organizational support, both in terms of justice, superior support, as well as awards and the work environment; and (c) There is a significant negative relationship between Perceived Organizational Support (POS) and workload. This finding indicates that the higher the perceived organizational support of courier partners, the lower their perceived workload. Conversely, lower perceived organizational support tends to be associated with increased workload experienced by Shopee Express courier partners.